Quantum system behaviour of Jaynes-Cummings model with Kerr-like medium - Chan, Yeen Chia (2016)
Jaynes-Cummings model is widely used to represent a quantum system as it is able to explain quantum behaviour in a more accurate and simple way. To date, the study of Jaynes-Cummings model does not involve multi-photon transitions and also three-qubit quantum entanglement, both coupled with Kerr-like medium. Thus the main objective of this study is to discover new behaviour for quantum system under these two conditions coupled with Kerr-like medium. In achieving this objective, Jaynes-Cummings model is modified to include multi-photon transition and three-qubit quantum system coupling with Kerr-like medium. Under the multi-photon transition condition, Pegg-Barnett formalism is used to measure the quantum system behaviour in the modified Jaynes-Cummings model. The result shows that as the strength of the coupling increases, the quantum system behaviour becomes more active. However, as the number of photons transition increases, the influence from Kerr-like medium towards quantum system behaviour decreases. Next, under the three-qubit quantum system with one-photon transition condition, the three-qubit state interacts with Markovian and non-Markovian environments, both represented by Lorenztian spectral density. The lower bound concurrence is used to measure quantum entanglement robustness. Result shows that when Kerr-like medium coupling strength is increased for both Markovian and non-Markovian environments, the quantum entanglement are more robust. Concurrently, the influence of quantum entanglement robustness is reduced when dipole-dipole interaction is getting stronger. As a conclusion, this study discovered new quantum system behaviour under the influence of Kerr-like medium with potential application in quantum information processing.